2019
DOI: 10.1590/1806-9061-2018-0930
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Chemical and Sensorial Quality of Eggs Coated With Copaiba Oil Biofilm and Stored At Room Temperature for Different Periods

Abstract: The present study aimed at evaluating the effects of a coating based on copaiba oil on the quality of eggs stored for different periods. Eggs were coated with copaiba oil solutions (4, 8, 12, 16, or 20% copaiba oil) or not (control) and stored for 1, 7, 14, 21, 28 or 35 days at room temperature. The following parameters were evaluated: egg weight loss, egg components (albumen, yolk, and eggshell) relative weights, egg specific gravity, Haugh units, eggshell quality, and sensorial attributes. Eggs stored for 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Five eggs from each treatment underwent a physical quality analysis according to the methods described by Brasil et al (2019). Measurements included egg weight; percentages, heights, circumferences and pH values of the yolk and albumen; yolk color on a scale from 1 to 15 using a graduate fan; and eggshell characteristics including weight, percentage and thickness (measured in the basal, meridional, and apical regions).…”
Section: Physical Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Five eggs from each treatment underwent a physical quality analysis according to the methods described by Brasil et al (2019). Measurements included egg weight; percentages, heights, circumferences and pH values of the yolk and albumen; yolk color on a scale from 1 to 15 using a graduate fan; and eggshell characteristics including weight, percentage and thickness (measured in the basal, meridional, and apical regions).…”
Section: Physical Qualitymentioning
confidence: 99%
“…Several techniques and products have been studied to conserve the internal and external quality of eggs at room temperature, and provide alternatives for these production chains. Coating treatments applied to the eggshell surface have been reported as particularly effective measures, acting like "artificial cuticles" that decrease gas exchange through the eggshell and maintain the egg's quality attributes for an extended duration (Biladeau & Keene, 2009;Pissinati et al, 2014;Brasil et al, 2019). According to Waimaleongora-Ek et al (2009) and Brasil et al (2019), an oil-based coating has demonstrated substantial efficacy in retarding egg weight loss and maintaining internal quality due to its hydrophobic properties.…”
Section: Introductionmentioning
confidence: 99%
“…As aves tiveram seu desempenho avaliado de acordo a metodologia descrita por Rufino et al (2021), sendo a cada período de 21 dias aferidos o consumo de ração animal (g/ave/dia), consumo de proteína (g/ave/dia), consumo de energia (g/ave/dia), produção de ovos (%), conversão alimentar (kg de ração por kg de ovo produzidokg/kg), conversão alimentar (kg de ração por dúzia de ovos produzidoskg/dz) e massa de ovos (g) de cada repetição. Nos dois últimos dias de cada período, quatro ovos de cada repetição foram selecionados aleatoriamente para analisar a sua qualidade de acordo com a metodologia descrita por Brasil et al (2019) e Rufino et al (2021). As variáveis de qualidade dos ovos avaliadas foram: o peso do ovo (g), percentagem de albúmen (%), percentagem de gema (%), percentagem de casca (%), altura do albúmen (mm), altura da gema (mm), diâmetro da gema (mm), espessura da casca (μm), gravidade específica (g/cm 3 ), unidade Haugh e coloração da gema.…”
Section: Análises Experimentaisunclassified
“…Although eggs are an animal protein source, their importance in human nutrition is high due to containing unsaturated fatty acids, vitamins, and minerals (Şenköylü 2001;Sarıca and Erensayın 2014;Puglisi and Fernandez 2022;Tian et al, 2022). An egg obtained from a healthy animal has the highest quality value at the moment it is laid, but its quality may decrease depending on storage conditions, leading to marketing problems (Aygun 2017;Brasil et al, 2019;Yenilmez and Bulancak 2020;Sariyel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%